Mobile assisted language learning (MALL) in developing second language learners’ understanding of grammar - Abdul Ghani, Rozina; Tengku Paris, Tengku Nazatul Shima; Ahamad Shah, Mohamed Ismail; L. Y., Rahmah; A., Hafiza (Universiti Teknologi MARA (UiTM) Negeri Sembilan, 2017)
This paper presents findings to a case study on the use of ‘Throw Back Time’ (TBT), a digital game aimed at teaching grammar tenses and aspects via Mobile Assisted Language Learning (MALL). A quantitative study by means of a time series pre-test/post-tests single group design and survey were used as to see whether the game could improve learners’ understanding and knowledge of grammar tenses and aspects and also at gauging the learners’ perceptions towards MALL in learning grammar. The game is specially designed according to the Theory of Variation (Marton & Booth, 1997) that emphasizes that students understand, experience and think differently in a specific aspect of the world. As variations in the learning outcome are necessary, the game provides a variety of combinations and structures of grammatical aspects to expose students to different aspects from the object of learning. The application of this strategy in the digital game is part of a major research which aims at presenting empirical evidence of an innovative way to teach grammar. A digital board game suited to the students’ level of English can be an intriguing practice in the process of learning as the teaching and learning of grammar can be a daunting experience for learners and teachers alike. Thus, traditional methods must inevitably be on par with the advent of technology to complement the teaching of grammar and enhance the development of students’ knowledge of grammar.